PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING DALAM PENERIMAAN KARYAWAN PADA PT. MUSTIKA MAJU MANDIRI - Opik Widayat; Farida Nurlaila (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
One of the most important activities in a company or organization is the problem of human resources. Because, the main focus of human resource management is to contribute to the success or failure of a company. PT. Mustika Maju Mandiri is a company engaged in computers and technology. Selection of employee acceptance is one of the problems that have occurred so far. in the process of hiring production employees at PT. Mustika Maju Mandiri, the personnel department chooses and selects one by one the incoming applicant data. If the data is complete, the personnel department will call the applicant to take part in the selection process. The large number of applicants makes personnel often experience difficulties in selecting prospective employees, and in the selection process the decisions taken are often influenced by the subjectivity of decision makers. The Decision Support System for Selection of Employee Candidates can assist HRD/Personnel in recruiting prospective employees according to qualifications. In conducting recruitment, the selection of prospective employees according to company qualifications with the results of calculating the graduation criteria for prospective employees according to company qualifications is 80%.